Reducing Potato Cyst Nematode Attack on Granola L. with in-Vitro and ex-Vitro G0 Seed Production - Yusianto, Rindra; Marimin, Marimin (Faculty of Agriculture, Universitas Malikussaleh, 2024)
Potato Cyst Nematode/PCN (Globodera rostochiensis) attack is the most critical risk in potato farming. The attack was marked by a decrease in the production of up to 60%. The objectives of this study were to reduce postharvest losses due to PCN attacks on Granola L and to compare yields from G2 and G0 seeds. This research was conducted in 5 districts (N1, N2, N3, N4, and N5) in Wonosobo Regency, Central Java, Indonesia. The method used in this study was the comparison of yields from G2 and G0 seeds in the same area, considering temperature (V1) and altitude (V2). The results showed that Granola L from G2 seeds for 100 days after planting was 15.9 tons/ha, while the results for G0 seeds in the same field increased to 12.18 tons/ha. In G2 seeds, 52 cysts/100 ml of soil were obtained, while in G0 seeds, cysts were not accepted. Combining G0 seeds in vitro and ex-vitro on Granola L can reduce PCN attacks and increase yields by up to 73%. Conducting experiments with other cultivars, such as the Atlantic and Agria, is necessary for further research.